Association of Job Characteristics and Burnout of Healthcare Workers in Different Positions in Rural China: A Cross-Sectional Study - Mei Zhang; Sangsang Li; Dan Han; Yunyi Wu; Jie Zhao; Hui Liao; Ying Ma; Chaoyang Yan; Jing Wang; Jing Wang; Jing Wang (International Journal of Public Health, 2023)
Objectives: Health workers in rural primary care systems are at increased risk of job burnout, but their associations with different positions have received scant attention in the literature. Thus, this study aims to measure job burnout in different positions in rural China and to identify factors associated with it.Methods: A cross-sectional survey was conducted with a total of 15,627 participants from six provinces in China. And job burnout was measured using the Chinese version of the Maslach Burnout Inventory-General Scale (MBI-GS). Multilevel regression analyses were used in examining factors potentially associated with job burnout in different positions.Results: Overall, more than half of providers suffered from moderate burnout. The degree of job burnout varied among different positions. Middle managers showed higher levels personal stress, while general staff showed the lowest interpersonal and self-evaluation dimensions of burnout. Job duty, job capability, job treatment, and career advancement are potential factors affecting these results.Conclusion: Interventions aimed at providing appropriate training and development opportunities, developing relevant career planning and management strategies, and implementing reasonable staffing and job design may be promising strategies for alleviating burnout in different positions and improving health system performance.